Effect of Gum Chewing for Early Restoration of Bowel Activity after Cesarean Section - Anum Dilshad, Rabia Dilshad, Nadia Babar, Gulshan Ayesha (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative ileus is a common concern following cesarean section, leading to delayed gastrointestinal recovery. Chewing gum has emerged as a simple and non-invasive intervention to enhance bowel motility through the cephalic vagal reflex and stimulation of gastrointestinal hormone secretion, thereby promoting the early return of bowel sounds and passage of flatus. Objective: This study aimed to compare the mean postoperative time interval for the return of bowel sounds and the first passage of flatus between women who chewed gum and those who did not following a cesarean section. Methods: A prospective, randomized controlled trial was conducted at the Department of Obstetrics and Gynecology, Bahawalpur Victoria Hospital, Bahawalpur, over a six-month period after ethical approval. A total of 60 women aged 18 to 40 years undergoing elective cesarean section were included. Patients with electrolyte imbalances, diabetes, or prior intra-abdominal surgery were excluded. Participants were randomly allocated into two groups: Group A (gum chewing) and Group B (non-gum chewing). Women in Group A received one stick (5 grams) of chewing gum three times a day for one hour, starting six hours postoperatively, while Group B received standard postoperative care without gum chewing. The primary outcomes were the mean time to the first auscultation of normal bowel sounds and the first passage of flatus. Results: The mean age of patients in Group A was 30.20 ± 4.24 years, and in Group B, it was 29.87 ± 4.28 years. The mean time to the return of bowel sounds in Group A was significantly shorter (10.60 ± 1.90 hours) compared to Group B (16.03 ± 2.63 hours) (p < 0.0001). Similarly, the mean time to the first passage of flatus was significantly reduced in Group A (18.67 ± 2.38 hours) compared to Group B (25.63 ± 2.89 hours) (p < 0.0001). Conclusion: Chewing gum significantly reduces the time to the return of bowel sounds and the first passage of flatus following cesarean section, suggesting its effectiveness as a simple and safe intervention to enhance postoperative gastrointestinal recovery. Keywords: Cesarean section, chewing gum, gastrointestinal motility, postoperative ileus, passage of flatus.